Comparison of measuring energy expenditure with indirect calorimetry and traditional estimation of energy expenditure in patients in intensive care unit - Xiao, Gui-zhen (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2011)
OBJECTIVE: To compare measurement of energy expenditure (MEE) by indirect calorimetry (IC) with traditional estimation of energy expenditure (EEE), to provide a basis for energy supplementary for critically ill patients